In between home and homeland: Diaspora identity as a cultural hybrid in Mohsen Namjoo's "Cielito Lindo". (3rd July 2017) - Steward, Theresa Parvin
ABSTRACT: Rather than resisting either new or old culture, Iranian musicians in the diaspora embrace both their new host environments and their native homeland, as they create a place between cultural assimilation and preservation, helping to shape new sounds of exile. This essay explores how Iranian musicians embrace the new and the familiar, the traditional and the popular, creating an original cultural hybrid. Questions of cultural identity and the politics of location and displacement are addressed using a theoretical cultural studies framework, incorporating themes of personal and collective nostalgia. This discussion is supplemented by documented narrative experiences from Iranian musicians and artists. Furthermore, the textual and musical analysis of singer-songwriter Mohsen Namjoo's readaptation of the familiar Mexican ranchera song "Cielito Lindo" uncovers unique nuances and layers of meaning that not only shed light on one musician's personal journey to exile, but also speak to a greater collective experience of Iranians today who continue to be torn between home and homeland.